Digital Transformation Policy in Japan: the Case of Artificial Intelligence - K. S. Kostyukova (Модернизация, инновация, развитие)
Purpose: this article includes the review of the Japanese policy on the national economy Digital Transformation, using the case of implementation of artificial intelligence for production and services, description and analysis of the current results, as well as identification of obstacles to achieve the expected results. Methods: the article is based on the analysis of scientific and analytical materials to the problem of research. The factual basis is the framework documents of the Cabinet of Japan, media, reports on research conducted by Japanese research institutes. Results: the article provides a brief review and analysis of the Japanese public policy of the development of AI technology, summarizes the interim results of the measures taken, identifies problematic factors that prevent the achievement of the expected results. The hypothesis is put forward about the insufficiency of government efforts to monitor and analyze the activities already implemented, the lack of practice of taking into account failures in the formation of new programs and projects. Recently, significant attention to the development of AI technology is paid in Russia. In 2019, Russian President Vladimir Putin approved the "National strategy for the development of AI until 2030". It is expected that the using of digital technologies, will increase the competitiveness of the national economy, improve the welfare of society. In this regard, the study of Japan's experience as one of the technological leaders in the development and using of digital transformation, is especially important. Conclusions and Relevance: To solve the current socio-economic problems, Japan government relies on the development of the advanced technologies. At the same time, the government continues to develop measures to stimulate the cooperation of the academic and industrial sectors to conduct joint R&D on priority technologies. However, due to the "closed" nature of Japanese corporations and the relative independence of government plans in determining the technological priorities development, the corporate sector is reluctant to follow government recommendations on the using new technologies in management and production processes, as well as joint projects with the academic sector are not large-scale and are rather formal. This situation indicates the continuing unpreparedness of key NIS participants for the perception of the advanced technologies and digital transformation.